Natural disaster death and socio-economic factors in selected Asian countries: a panel analysis - Padli, Jaharudin; Habibullah, Muzafar Shah (Canadian Center of Science and Education, 2009)
The purpose of the present study is to investigate the relationship between disaster fatalities with the level of economic development, years of schooling, land area and population for a panel of fifteen Asian countries over the sample period over 1970 to 2005. Our results indicates that the relationship between disaster losses and the level of economic development is nonlinear in nature suggesting that at lower income level, a country is more disaster resilience but at higher income level, an economy become less disaster resistant. Other disaster determinants of interest is the level of education which suggests that educational attainment reduces human fatalities as a result of disaster; larger population will increase death toll and larger land area will reduce disaster fatalities.